2016
DOI: 10.5688/ajpe8010175
|View full text |Cite
|
Sign up to set email alerts
|

Combination of a Flipped Classroom Format and a Virtual Patient Case to Enhance Active Learning in a Required Therapeutics Course

Abstract: Objective. To design and evaluate the integration of a virtual patient activity in a required therapeutics course already using a flipped-classroom teaching format. Design. A narrative-branched, dynamic virtual-patient case was designed to replace the static written cases that students worked through during the class, which was dedicated to teaching the complications of liver disease. Students completed pre-and posttests before and after completing the virtual patient case. Examination scores were compared to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 25 publications
1
50
0
1
Order By: Relevance
“…Both early and more advanced learners practice and learn key patient care outcomes of the profession through repetitive, “real‐life” scenarios. We have utilized VPs to supplement lecture, to replace lecture, and to assess knowledge and skill . Most recently, VPs have been incorporated into authentic assessment deployed as a blended simulation progress test of learner readiness for practice .…”
Section: Computer‐based Simulation and Virtual Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both early and more advanced learners practice and learn key patient care outcomes of the profession through repetitive, “real‐life” scenarios. We have utilized VPs to supplement lecture, to replace lecture, and to assess knowledge and skill . Most recently, VPs have been incorporated into authentic assessment deployed as a blended simulation progress test of learner readiness for practice .…”
Section: Computer‐based Simulation and Virtual Patientsmentioning
confidence: 99%
“…Although simulation education had been implemented in military, medical, and nursing programs for decades, the use of high‐fidelity human patient simulation in pharmacy education was first documented in 2006 . Since then, there has been a growth of implementation, outcomes, and assessment of simulation in addition to the expansion of virtual patients (VPs), simulated electronic health records (EHRs), and gaming strategies throughout clinical pharmacy education. As the pedagogical options grow in number and complexity, it is an opportune time to provide clarity in language for the field of health care education.…”
Section: Introductionmentioning
confidence: 99%
“…Fifty‐nine percent of students also wanted to see more cases incorporated throughout the course. A recent study evaluated the use of one virtual patient case in one required therapeutics course using a flipped‐classroom teaching format . Similar to the previous study, the case incorporated a branched‐narrative, decision‐making teaching model and pre‐simulation/post‐simulation tests were used.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to CBL, flipped classroom pedagogy has attracted the attention of educators and has been widely implemented and studied in many disciplines, including nursing [16][17][18][19]. Some studies have found that the strategy of flipped classroom in nursing education presents certain advantages over traditional lecture-based learning in terms of improving students' examination scores, grades and satisfaction [20,21].…”
Section: Case-based Learning and The Flipped Classroom Are Feasible Imentioning
confidence: 99%